Estructura organizacional y relaciones en el entorno socioeconómico de la Universidad Laica “Eloy Alfaro” de Manabí y Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” para la transferencia de conocimientos científico-tecnológicos - Bravo Mendoza, Angélica Elizabeth (2020)
In the present investigation, with the objective of carrying out a comparative study between the ULEAM universities and the ESPAM MFL within the organizational structure and relations with the socioeconomic environment for the transfer of scientific-technological knowledge, we proceeded from scientific and legal theories that gave credibility to the research. In this way, when diagnosing the organizational structure of educational institutions with respect to the transfer of scientific-technological knowledge to the socioeconomic environment, it was established that it has a mission, vision and organic structure of the departments and obligations that each institution has, which are located in different areas due to their hard work inside and outside the institution since they require their own space to optimally perform their functions. Subsequently, techniques such as a survey of the teachers of the institutions were used with the aim of knowing how the transfer of knowledge is carried out in the universities and their relationship with the environment. The results revealed the participation of the aforementioned universities in linked projects in recent years; subsequently, the number and type of companies benefited by the field of action of knowledge transfers in the executed projects were determined, where it was shown that ESPAM MFL has had agreements with 6 companies and ULEAM with 8 companies in the last 2 years.